Single-Cell Transcriptome Comparison of Bladder Cancer Reveals Its Ecosystem - Luo, Yongxiang; Tao, Tao; Tao, Ran; Huang, Guixiao; Wu, Song (Frontiers in Oncology, 2022)
Bladder carcinoma (BLCA) is a highly heterogeneous disease, and the underlying biological behavior is still poorly understood. Here, single-cell RNA sequencing was performed on four clinical samples of different grades from three patients, and 26792 cell transcriptomes were obtained revealing different tumor ecosystems. We found that N-Glycan biosynthesis pathway was activated in high-grade tumor, but TNF-related pathway was activated in cystitis glandularis. The tumor microenvironment (TME) of different samples showed great heterogeneity. Notably, cystitis glandularis was dominated by T cells, low-grade and high-grade tumors by macrophages, while TME in patient with high grade relapse by stromal cells. Our research provides single-cell transcriptome profiles of cystitis glandularis and BLCA in different clinical states, and the biological program revealed by single-cell data can be used as biomarkers related to clinical prognosis in independent cohorts.